Right-lateralized unconscious, but not conscious, processing of affective environmental sounds. Issue 4 (1st November 2016) - Schepman, Astrid; Rodway, Paul; Pritchard, Hayley
ABSTRACT: Much research on the laterality of affective auditory stimuli features emotional speech. However, environmental sounds can also carry affective information, but their lateralized processing for affect has been studied much less. We studied this in 2 experiments. In Experiment 1 we explored whether the detection of affective environmental sounds (from International Affective Digital Sounds) that appeared in auditory scenes was lateralized. While we found that negative targets were detected more rapidly, detection latencies were the same on the left and right. In Experiment 2 we examined whether conscious appraisal of the stimulus was needed for lateralization patterns to emerge, and asked participants to rate the stimuli's pleasantness in a dichotic listening test. This showed that when positive/negative environmental sounds were in the attended to-be-rated channel, ratings were the same regardless of laterality. However, when participants rated neutral stimuli and the unattended channel was positive/negative, the valence of the unattended channel affected the neutral ratings more strongly with left ear (right hemisphere, RH) processing of the affective sound. We link our findings to previous work that suggests that the RH may specialize in the unconscious processing of emotion via subcortical routes.